Assessment of the bycatch level for the Black Sea harbour porpoise in the light of new data on population abundance - Popov, Dimitar; Meshkova, Galina; Vishnyakova, Karina; Ivanchikova, Julia; Paiu, Marian; Timofte, Costin; Amaha Öztürk, Ayaka; Tonay, Arda M.; Dede, Ayhan; Panayotova, Marina; Düzgüneş, Ertuğ; Gol’din, Pavel (Frontiers in Marine Science, 2023)
Incidental catch in fishing gear (often known as bycatch) is a major mortality factor for the Black Sea harbour porpoise (Phocoena phocoena relicta), an endemic subspecies listed as Endangered in the IUCN Red List. The primary gear, responsible for porpoise bycatch in the Black Sea are bottom gillnets and trammel nets targeting turbot (Scophthalmus spp.), the most valuable commercial fish species in the Black Sea. From 2019 to 2021, a study was conducted in Bulgaria, Romania, Türkiye and Ukraine, to estimate the bycatch level in light of new information on porpoise distribution and abundance obtained from aerial surveys (CeNoBS) undertaken in 2019 as part of ACCOBAMS Survey Initiative (ASI). Bycatch data were collected by independent observers onboard turbot fishing boats (Bulgaria and Romania), complemented by questionnaire surveys and examination of stranded carcasses (in all countries). Some 48 monitoring trips took place (63 hauls by 11 different vessels). Cetaceans were caught on just over half of the trips (55%): 182 harbour porpoises, 4 bottlenose dolphins and 3 common dolphins. The median number of porpoises bycaught per trip was 1 (maximum 41) and the number of porpoises per km of net varied between 0 and 3.66 (median 0.1). Bycatch rates showed seasonal variation with marked increase in summer, compared to spring. The total annual bycatch of harbour porpoises in the Black Sea was roughly estimated as between 11 826 and 16 200 individuals. These numbers were the product of median values for effort (days/trips and vessels) and bycatch rate. Given the new estimates of porpoise abundance based on the CeNoBS survey of 2019 and reconciling abundance and bycatch estimates, harbour porpoise bycatch in the Black Sea represents between 4.6% - 17.2% of the estimated total population, depending on assumptions used. Even the most conservative estimate is among the highest worldwide and far exceeds the probable sustainable levels of around 1.0-1.7%. This study confirms that bycatch poses the most serious threat to the Black Sea harbour porpoises and that all riparian countries engaged in turbot fisheries must implement urgent measures to reduce it immediately, if the population is to survive in the long-term.